The intermodal transport system as a factor of the national economy competitiveness in the world market - A. V. Verigina (Учёт. Анализ. Аудит)
The article considers the essence of intermodal transportation, determines its main advantages for both parties of the cargo transportation process, and presents the composition of existing intermodal complexes as the main part of the functioning of the country’s transport system. The emphasis is made on the specifics of the modern customer-centered economy, which directly affects the organization of international transportation. In the paper, the author uses both qualitative and quantitative methods of analyzing research data provided by other authors as well as retrospective statistical data. A comparative analysis of the work of successful companies in the field of intermodal transport is made. The ways to increase the competitiveness of the Russian economy in the world market through the development of modern logistics schemes for the movement of goods are considered. The article describes the activities of domestic companies, their features, shortcomings and methods of work in the context of the globalization of the economy with a graphical interpretation of the models used by them. The practical recommendations to improve the functioning of the objects of research are given.